Students’ Mathematical Spatial Ability in Terms of Gender: A Case Study of A Female Student with High Mathematical Spatial Ability - Baihaqi, Achmad; Supiat (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
This study was motivated by the contradiction between the general assumption that male students have higher mathematical spatial abilities than female students and the findings of a female student who shows high mathematical spatial performance. In addition, in-depth studies of female students with high mathematical spatial abilities are still limited in the literature. This study aims to find out “how” and “why” a female student has high mathematical spatial ability. This research uses a qualitative type with a case study design and an interpretative approach. The research subject was a female student at SMPN 68 Jakarta who was identified as having high mathematical spatial ability based on the initial observation of 66 students. Data were collected through the administration of three sets of mathematical spatial ability problems, semi-structured interviews, and non-systematic observations. The results showed that the female student was able to solve the spatial problems consistently and obtained the maximum score in all three problem sets. She showed a systematic solution strategy by reading and thoroughly understanding the information in the problem, and using her spatial imagination. Factors that support the student’s high mathematical spatial ability include learning that encourages concept understanding, independent learning habits, involvement in tutoring and private lessons, experience participating in math olympiads, support from family and friends, and the habit of playing space-based games. Abstrak: Penelitian ini dilatarbelakangi oleh adanya kontradiksi antara asumsi umum yang menyatakan bahwa siswa laki-laki memiliki kemampuan spasial matematis lebih tinggi dibandingkan siswa perempuan dengan temuan seorang siswa perempuan yang justru menunjukkan performa spasial matematis tinggi. Selain itu, kajian mendalam terhadap siswa perempuan dengan kemampuan spasial matematis tinggi masih terbatas dalam literatur. Penelitian ini bertujuan untuk mengetahui “bagaimana” dan “mengapa” seorang siswa perempuan memiliki kemampuan spasial matematis tinggi. Penelitian ini menggunakan penelitian kualitatif dengan desain studi kasus dan pendekatan interpretatif. Subjek penelitian adalah seorang siswa perempuan di SMPN 68 Jakarta yang teridentifikasi memiliki kemampuan spasial matematis tinggi berdasarkan hasil observasi awal terhadap 66 siswa. Data dikumpulkan melalui pemberian tiga paket soal kemampuan spasial matematis, wawancara semi terstruktur, dan observasi non-sistematis. Hasil penelitian menunjukkan bahwa siswa perempuan tersebut mampu menyelesaikan soal-soal spasial secara konsisten dan memperoleh skor maksimal pada ketiga paket soal. Ia menunjukkan strategi penyelesaian yang sistematis, dengan membaca dan memahami secara menyeluruh informasi pada soal, serta menggunakan pengimajinasian spasialnya. Faktor-faktor yang mendukung kemampuan spasial matematis tinggi siswa tersebut antara lain pembelajaran yang mendorong pemahaman konsep, kebiasaan belajar mandiri, keterlibatan dalam bimbingan belajar dan les privat, pengalaman mengikuti olimpiade matematika, dukungan dari keluarga dan teman, serta kebiasaan bermain game berbasis ruang.